Measuring the Role of Subnational Governments - Levin, Jonathan (IMF Working Papers; Working Paper ;, 1991)
To measure subnational governments, only external money flows are counted, excluding intra-level transactions in measuring a level of government and all intergovernmental transactions in measuring general government. Control, finance, and administration should be distinguished in measuring centralization and each level's share of general government, administered expenditures being net of grants given to other governments and financed expenditures net of grants received. Disparate decentralization of finance, control, and administration brings vertical imbalance, measured by the portion of a government's expenditures not covered by its own resources and by the ratio of intergovernmental grants to total government expenditures.